Spatial and Temporal Distribution of Water Plant Based on Satellite Imagery and the Effect in Jatiluhur Reservoir - Rahman, Arip; Anwar Putri, Masayu Rahmia; Purnamaningtyas, Sri Endah; Astuti, Lismining Pujiyani; Warsa, Andri (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Water vegetation in lakes or reservoirs can change the water's ecology. Water vegetation in Jatiluhur Reservoirs is dominated by water hyacinth (Eichhornia crassipes). Water hyacinth in lakes or reservoirs becomes an invasive weed that can cause ecological degradation. Jatiluhur Reservoir is one of the water bodies affected by the uncontrolled growth of water vegetation. The study was conducted to determine the spatial and temporal distribution patterns of water vegetation and its effect on Jatiluhur Reservoir. Water vegetation's spatial and temporal distribution was analyzed using Sentinel-2A satellite image data. The Normalized Difference Vegetation Index (NDVI) algorithm was used to see the distribution of water vegetation in the reservoir waters. The observations show that the movement of water vegetation starts from the inlet area and then moves along with the flow of water to the center of the reservoir. Finally, it accumulates in the outlet area. The correlation between vegetation cover area and month of observation obtained the equation y=662.5x + 128.1. Based on the equation, the increasing vegetation cover area in the Jatiluhur Reservoir is predicted to reach 128.1 ha per month. The physical method used for controlling the growth and distribution of vegetation (water hyacinth) in Jatiluhur Reservoir by taking in the waters. Efforts to control vegetation physically must notice the increasing rate of water hyacinth distribution.